2020
DOI: 10.1097/pg9.0000000000000017
|View full text |Cite
|
Sign up to set email alerts
|

Upper Gastrointestinal Bleeding as the First Presentation of Eosinophilic Gastrointestinal Disease

Abstract: Gastrointestinal bleeding is a rare but potentially life-threatening manifestation of eosinophilic gastrointestinal disorders (EGIDs). Here, we describe a case series comprising 5 pediatric patients between 7 and 12 years of age, who presented to the emergency department with hematemesis and were subsequently diagnosed with EGID. Accompanying allergic history, peripheral eosinophilia, and total IgE elevation were common. Despite a more severe presentation, response to medical and dietary therapy was favorable.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…Additionally, symptomology of EG at presentation was also observed to be different when compared to EoE. We found that GI bleeding featured strongly in our cohort of patients regardless of age of onset, similar to a recently published review by Ozdogan et al, 12 which described GI bleeding as a frequent initial presenting symptom of EG.…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, symptomology of EG at presentation was also observed to be different when compared to EoE. We found that GI bleeding featured strongly in our cohort of patients regardless of age of onset, similar to a recently published review by Ozdogan et al, 12 which described GI bleeding as a frequent initial presenting symptom of EG.…”
Section: Discussionsupporting
confidence: 89%
“…In our study, hematemesis occurred in 1 patient during the build‐up phase of OIT, which is an uncommon symptom of EoE, especially in children. However, several case series have been published that hematemesis occurred in 1.4% of children with EoE (35).…”
Section: Discussionmentioning
confidence: 99%